2020 IEEE 16th International Conference on Automation Science and Engineering (CASE) 2020
DOI: 10.1109/case48305.2020.9217017
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Voting-based Multi-class Prediction for Ore Selection

Abstract: Sensor-based intelligent sorting technology is a mineral separation technology with the merits of high-efficiency, energy-saving and water-saving. However, the prediction accuracy of conventional machine learning methods is unstable in multi-class selection of ores. The purpose of this study is to propose a competitive voting method to improve the multi-class prediction accuracy of ores in machine vision-based sorting system by combining the classification advantages of various machine learning methods. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Numerous studies of sorting using optical/infrared imaging were identified within the review [19,22,24,[28][29][30][31][32][33][34][35]. It was found that optical and infrared imaging were suitable for sorting a wide range of ores including coal, copper, gold, lead, marble, mineral sands, rare earth elements, tin and zinc.…”
Section: Optical and Hyperspectral Imagingmentioning
confidence: 99%
“…Numerous studies of sorting using optical/infrared imaging were identified within the review [19,22,24,[28][29][30][31][32][33][34][35]. It was found that optical and infrared imaging were suitable for sorting a wide range of ores including coal, copper, gold, lead, marble, mineral sands, rare earth elements, tin and zinc.…”
Section: Optical and Hyperspectral Imagingmentioning
confidence: 99%
“…In the field of mineral processing, Sensor-based ore sorting is a vital component as it enhances ore grades and minimizes the amount of waste material that is processed [5]. Evidence demonstrates that it effectively decreases the usage of energy, water, and reagents, while also minimizing the formation of fine waste, by disposing of trash before undergoing additional processing [6], [7]. To successfully apply sensor-based sorting, it is crucial to select a sensing approach that can efficiently distinguish between ore and waste [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of mineral processing, Sensor-based ore sorting is a vital component as it enhances ore grades and minimizes the amount of waste material that is processed 6 . Evidence demonstrates that it effectively decreases the usage of energy, water, and reagents, while also minimizing the formation of fine waste, by disposing of trash before undergoing additional processing 7,8 . To successfully apply sensor-based sorting, it is crucial to select a sensing approach that can efficiently distinguish between ore and waste 9 .…”
mentioning
confidence: 99%